MAPLE Fabricated Fe3O4@Cinnamomum verum Antimicrobial Surfaces for Improved Gastrostomy Tubes - Alina Georgiana Anghel; Alexandru Mihai Grumezescu; Mariana Chirea; Valentina Grumezescu; Gabriel Socol; Florin Iordache; Alexandra Elena Oprea; Ion Anghel; Alina Maria Holban (Molecules, 2014)
Cinnamomum verum-functionalized Fe3O4 nanoparticles of 9.4 nm in size were laser transferred by matrix assisted pulsed laser evaporation (MAPLE) technique onto gastrostomy tubes (G-tubes) for antibacterial activity evaluation toward Gram positive and Gram negative microbial colonization. X-ray diffraction analysis of the nanoparticle powder showed a polycrystalline magnetite structure, whereas infrared mapping confirmed the integrity of C. verum (CV) functional groups after the laser transfer. The specific topography of the deposited films involved a uniform thin coating together with several aggregates of bio-functionalized magnetite particles covering the G-tubes. Cytotoxicity assays showed an increase of the G-tube surface biocompatibility after Fe3O4@CV treatment, allowing a normal development of endothelial cells up to five days of incubation. Microbiological assays on nanoparticle-modified G-tube surfaces have proved an improvement of anti-adherent properties, significantly reducing both Gram negative and Gram positive bacteria colonization.